Aplikasi perangkat lunak AFES untuk perancangan pondasi dangkal pada kandang ayam close house di Politeknik Negeri Tanah Laut - Norminawati Dewi; Muhammad Azhar; Muhammad Rizan Adam (Program Studi Teknik Sipil, Fakultas Teknik dan Perencanaan, Universitas Warmadewa, 2024)
The construction of a poultry house with a close house system at Politeknik Negeri Tanah Laut aims to support student learning and research in modern agricultural practices. This facility integrates cutting-edge technology for optimal environmental control, providing a practical platform for academic. The primary focus of this study is to analyze soil investigation data and demonstrate the efficiency of shallow foundation design using the AFES software. Soil investigation at the project site revealed that the subsoil predominantly consists of clayey silt to silty clay, with depths ranging from 0.4 m to 6.6 m at borehole S1 and 0.6 m to 8.0 m at borehole S2. These findings provided essential input parameters for the foundation design process. Utilizing AFES software significantly streamlined the design workflow by offering three key outputs design drawings, 3D models, and detailed reinforcement and design criteria summarized in a comprehensive report. Additionally, the software generated a bill of materials, facilitating accurate cost estimation for the foundation construction. The results demonstrate the practical application of AFES in accelerating foundation design while maintaining accuracy and efficiency. This study underscores the importance of integrating advanced computational tools with thorough geotechnical investigation, offering a reliable and cost-effective foundation solution tailored to the unique requirements of the site.